(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Every day, huge numbers of people around the world go missing. These missing people include children, teenagers, mentally challenged individuals, elderly individuals with Alzheimer’s disease, etc.. Most of them remain untraced. This study offers a method that would help the police and the public by speeding the process of searching using face recognition. Face recognition technology may be utilized for various reasons and finding the missing individual is a biggest advantage for any face recognition approach. To make the work of discovering the missing person easier we are intending to build an application which will be accessed by certain volunteers via which we can find missing person in short span of time. The police will have an easier time finding a specific person as a result of this. However, in order to locate a certain person, it is necessary to automate the process by identifying a specific image and comparing it to other images. to check whether both photos having same qualities or not. By doing this we will come to know whether the missing person in the image clicked from certain location is correct or not, and if it is correct then police can start their following steps to find the individual from that region.